Cortical microstructure in the amyotrophic lateral sclerosis–frontotemporal dementia continuum. (3rd November 2020) - Illán-Gala, Ignacio; Montal, Victor; Pegueroles, Jordi; Vilaplana, Eduard; Alcolea, Daniel; Dols-Icardo, Oriol; de Luna, Noemi; Turón-Sans, Janina; Cortés-Vicente, Elena; Martinez-Roman, Luis; Sánchez-Saudinós, Maria Belén; Subirana, Andrea; et al.
Abstract : Objective: To characterize the cortical macrostructure and microstructure of behavioral and cognitive changes along the amyotrophic lateral sclerosis (ALS)–frontotemporal dementia (FTD) continuum. Methods: We prospectively recruited 88 participants with a 3T MRI structural and diffusion-weighted imaging sequences: 31 with ALS, 20 with the behavioral variant of FTD (bvFTD), and 37 cognitively normal controls. Participants with ALS underwent a comprehensive cognitive and behavioral assessment and were dichotomized into ALS without cognitive or behavioral impairment (ALSno-cbi; n = 12) and ALS with cognitive or behavioral impairment (ALScbi; n = 19). We computed cortical thickness and cortical mean diffusivity using a surface-based approach and explored the cortical correlates of cognitive impairment with the Edinburgh Cognitive and Behavioral ALS Screen. Results: The ALSno-cbi and ALScbi groups showed different patterns of reduced cortical thickness and increased cortical mean diffusivity. In the ALSno-cbi group, cortical thinning was restricted mainly to the dorsal motor cortex. In contrast, in the ALScbi group, cortical thinning was observed primarily on frontoinsular and temporal regions bilaterally. There were progressive cortical mean diffusivity changes along the ALSno-cbi, ALScbi, and bvFTD clinical continuum. Participants with ALS with either cognitive or behavioral impairment showed increased cortical mean diffusivity in the prefrontal cortex in the absence of cortical thickness. Conclusions: Cortical mean diffusivity might be a useful biomarker for the study of extramotor cortical neurodegeneration in the ALS-FTD clinical spectrum. Classification of evidence: This study provides Class III evidence that the cortical microstructure correlates with cognitive impairment in the ALS-FTD continuum.